Production of Eco-friendly Liquid Hand Soap Using Local Products for Community Empowerment - Anwar, M. Syaiful; Oktofan, Niko Ilham; Yu, Chen Bao (Bisma : Bimbingan Swadaya Masyarakat, 2024)
This community service project aimed to empower the Sedati, Sidoarjo community by producing eco-friendly liquid hand soap using local ingredients, specifically "daun sirih" (betel leaves). With the ongoing challenges of the COVID-19 pandemic, the project utilized a service-learning approach to educate local residents on sustainable soap production as part of the new normal. The activities included training on the benefits and production of hand soap from natural, environmentally friendly materials. The project not only contributed to public health efforts but also provided a low-cost, locally sourced alternative to commercial hand sanitizers. The participants, primarily housewives, gained new skills and knowledge in soap production, thereby increasing their awareness of eco-friendly practices and contributing to community resilience.